Indications for the laparoscopic approach to acute small bowel obstruction: A retrospective review of 50 cases, a literature review, and a single hospital's preliminary experience. Issue 2 (May 2016) - Cantarella, Francesco; Evoli, Luca Pio; Renzi, Claudio; Cavazzoni, Emanuel; Contine, Alessandro; Cesari, Maurizio; Donini, Annibale
Abstract: Small bowel obstruction (SBO) is mainly caused by postoperative adhesions, but a broad spectrum of diseases may cause this pathogenetic condition. Laparoscopic treatment represents an efficient approach to SBO. The aim of this paper was to review a single center's experience with a minimally invasive approach to multiple pathologic scenarios causing SBO. From January 2010 to December 2012, 50 consecutive patients underwent laparoscopic surgery for mechanical SBO. In 90% of patients, the surgical procedure was totally laparoscopic, while 10% required conversion to midline laparotomy. In‐hospital morbidity was 15% among totally laparoscopic patients and 40% among those who underwent conversion to midline laparotomy. Thirty‐day mortality was zero. One patient died 4 months postoperatively from neoplastic disease progression; the remaining patients were free from occlusive symptoms at follow‐up. The minimally invasive technique applies to a broad spectrum of cases. A larger cohort of patients seems necessary to reproduce our results and confirm the effectiveness of a laparoscopic approach to SBO.